An introduction to systematic reviews - Gough, David (David A.); Oliver, Sandy 1955-; Thomas, James 1983- (SAGE, 2017)
"Focused on actively using systematic review as method, An introduction to systematic reviews provides clear, step-by-step advice on the logic and processes of systematic reviewing. Stressing the importance of precision and accuracy, this practical text carefully balances a need for insightful theory with real-world pragmatism. The second edition features a new chapter on statistical synthesis and introduces a wide range of cutting-edge approaches to research synthesis, including text mining, living reviews, and new ideas in mixed methods reviews, such as qualitative comparative analysis"--Back cover.